Experimental study of CFDST columns infilled with UHPC under close-range blast loading. (July 2016) - Zhang, Fangrui; Wu, Chengqing; Zhao, Xiao-Ling; Xiang, Hengbo; Li, Zhong-Xian; Fang, Qin; Liu, Zhongxian; Zhang, Yadong; Heidarpour, Amin; Packer, Jeffrey A.
Highlights: CFDST columns can effectively withstand severe blast load without failure. The failure mode was global flexural response with no signs of steel buckling. The increase in explosive charge weight caused a larger mid-span deflection. The applied axial compressive load led to a reduction in the peak deflection. CFDST and CFST specimens yielded similar period of oscillation, peak and residual deflections. Abstract: Concrete-filled double-skin tubes (CFDST) have been increasingly popular in the field of engineering in recent years. A lot of research has been carried out to investigate the behaviour of CFDST members under a variety of loading conditions. This paper presents an experimental investigation on ultra-high performance concrete infilled double-skin tube columns subjected to close-in blast loading. Two types of CFDST columns were investigated in the experiments – one with both inner and outer tubes circular and the other one with both square. The main test parameters included the explosive charge weight and the magnitude of axial load. After the blast tests, there was no visible buckling nor ruptures found on the steel tubes and only minor cracks, of no more than 1mm width, were observed in the core concrete when the outer steel tube was removed. Based on the findings of the experiments, it is evident that CFDST column has excellent blast resistance. This feature has the potential to be used in high-value structures which may be the targets of terrorist attacks, such as embassies, government buildings and critical infrastructures.